Genomic analysis of co-infection with Wolbachia and Candidatus Tisiphia in the sand fly Sergentomyia squamirostris - Itokawa, Kentaro; Kuroki, Akihiro; Kobayashi, Daisuke; Kuroda, Makoto; Sawabe, Kyoko; Isawa, Haruhiko; Sanjoba, Chizu (Frontiers in Microbiology, 2025)
IntroductionEndosymbiotic bacteria show diverse strategies to manipulate host reproduction for their survival in nature. The diversity of symbionts infecting hematophagous insects and their impact on host ecology could be crucial for developing effective control measures of disease-transmitting vectors. Sand flies are a group of small insects, with some species serving as vectors for leishmaniasis, bartonellosis, and arboviral diseases. Sergentomyia squamirostris is the only known species of sand flies found on the main islands of Japan. Although no medical implications exist for S. squamirostris, we conducted whole-genome sequencing to explore its potential relevance.MethodsWe conducted whole-genome sequencing and de novo assembly of S. squamirostris using genomic DNA isolated from a single field-collected female insect sample. During this attempt, we incidentally obtained closed genomes of two new bacteria, wSSQ and RiSSQ, belonging to Wolbachia and Candidatus Tisiphia, respectively. We then investigated infection rates of both bacteria in two natural populations of S. squamirostris in Japan.ResultsPhylogenetic analysis indicated that wSSQ and RiSSQ belonged to Wolbachia and Ca. Tisiphia, respectively. Ca. Tisiphia is also known as “Torix Rickettsia,” which is considered a large group of endosymbionts of invertebrates with no known pathogenicity to humans and animals. NGS read depths for both wSSQ and RiSSQ genomes were found to be high coverages, indicating that these bacteria are S. squamirostris endosymbionts. The infection rates of wSSQ and RiSSQ in the wild population of S. squamirostris varied in the two different localities in Japan, and co-infection with both bacteria was commonly seen. wSSQ was detected in both sexes of S. squamirostris, whereas RiSSQ was detected only in female sand flies.ConclusionCa. Tisiphia has recently been recognized as an underexplored endosymbiont with a widespread presence in invertebrates, including disease vectors. RiSSQ represents the first complete genomic information resource of Ca. Tisiphia infecting sand flies. Further research is needed to understand potential interactions between its host and other endosymbionts, as well as to explore the potential implications of disease control in the future.